A new look at sodium channel β subunits. Issue 1 (January 2015) - Namadurai, Sivakumar; Yereddi, Nikitha R.; Cusdin, Fiona S.; Huang, Christopher L.-H.; Chirgadze, Dimitri Y.; Jackson, Antony P.
Abstract : Voltage-gated sodium (Nav ) channels are intrinsic plasma membrane proteins that initiate the action potential in electrically excitable cells. They are a major focus of research in neurobiology, structural biology, membrane biology and pharmacology. Mutations in Nav channels are implicated in a wide variety of inherited pathologies, including cardiac conduction diseases, myotonic conditions, epilepsy and chronic pain syndromes. Drugs active against Nav channels are used as local anaesthetics, anti-arrhythmics, analgesics and anti-convulsants. The Nav channels are composed of a pore-forming α subunit and associated β subunits. The β subunits are members of the immunoglobulin (Ig) domain family of cell-adhesion molecules. They modulate multiple aspects of Nav channel behaviour and play critical roles in controlling neuronal excitability. The recently published atomic resolution structures of the human β3 and β4 subunit Ig domains open a new chapter in the study of these molecules. In particular, the discovery that β3 subunits form trimers suggests that Nav channel oligomerization may contribute to the functional properties of some β subunits.